Eco-risk management of tylosin fermentation residues using vermicomposting. (1st February 2022) - Deng, Songge; Li, Peiyi; Wu, Yizhao; Tang, Hao; Cheng, Shujun; Thunders, Michelle; Qiu, Jiangping; Li, Yinsheng
Abstract: Tylosin fermentation residues (TFR) pose an ecotoxicological risk through antibiotic resistant bacteria (ARBs) and their corresponding genes (ARGs). This study evaluated the ecotoxicity of TFR to soil biological activity, and further explored the mechanisms of vermicomposting to reduce the toxicological risk. The results showed that tylosin (TYL) was moderately degradable with a half-life (t1/2 ) of 37.5 d, inducing 28–44% inhibition rate of nitrogen transformation in soil, and the EC50 of earthworm avoidance was 880 mg/kg. The 30-d vermicomposting reduced the pH and OM content, while increased the EC and TN content, accelerated compost maturation (C/N ratio up to 20), and enriched the microbial community. ARGs were reduced by earthworm through removal of TYL (>70% degradation, t1/2 of <20 d), inhibiting abundance of intI1 and ARBs. We conclude that vermicomposting is an efficient method for TFR treatment and its eco-risk management. Graphical abstract: Image 1 Highlights: Moderately degradable TYL in soil inhibited the activity of earthworm and microbiota. Vermicomposting promoted the compost efficiency and microbial community. ARGs were removed by earthworm reducing ARBs, intI1 and TYL (up to 70%).